Legal Responses to Online Hate Speech in India: Evaluating Section 66A and the Supreme Court’s Judgment in Shreya Singhal v. Union of India - Rahul D. Thakkar (Studies in Law and Justice, 2025)
This paper critically examines India’s legal responses to online hate speech through the lens of Section 66A of the Information Technology Act, 2000, and the landmark Supreme Court judgment in Shreya Singhal v. Union of India (2015). By tracing the evolution of Section 66A from its enactment to its judicial invalidation, the study highlights how vague legal provisions have been employed to suppress dissent in the digital space. The judgment in Shreya Singhal marked a doctrinal shift in Indian free speech jurisprudence by introducing constitutional tests of proportionality, precision, and incitement thresholds. Yet, post-judgment developments reveal persistent regulatory gaps, including the continued application of the repealed law and the emergence of executive-led content regulation under the IT Rules 2021. This paper argues for a reimagined legal framework grounded in rights-based, transparent, and procedurally robust safeguards that respect the normative centrality of freedom of expression in India’s digital democracy.